Safety and efficacy of a feed additive consisting of vitamin B2 (riboflavin) produced by Bacillus subtilis CGMCC 13326 for all animal species (Kempex Holland B.V.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2023)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) of EFSA was asked to deliver a scientific opinion on the safety and efficacy of vitamin B2 (riboflavin) produced by Bacillus subtilis CGMCC 13326 as a nutritional feed additive for all animal species. The additive is produced by a genetically modified production strain. Although the production strain harbours some genes coding for resistance to antimicrobials, viable cells and DNA of the production strain were not detected in the final product. Therefore, the use of B. subtilis CGMCC 13326 to produce vitamin B2 does not raise safety concerns. The use of riboflavin 80% produced by B. subtilis CGMCC 13326 in animal nutrition does not represent a safety concern for the target species, consumers and for the environment. In the absence of data, the FEEDAP Panel cannot conclude on the potential skin and eye irritation or potential toxicity by inhalation of the additive under assessment. Riboflavin is a known photosensitiser which may elicit skin and eye photoallergic reactions. The additive under assessment is effective in covering the animals' requirements of vitamin B2 when administered via feed.